Design And Build An Automatic Plant Sprinkler For A Farmer Group In Klino Village - Yussi Anggraini; Nikmatin Sholichah; Hodi Eko; Ganda Setiawan (International Journal Of Community Service, 2023)
This volunteer work is being done in Klino Bojonegoro, more specifically in the Bojonegoro and Madiun border region. By supplying IOT-based automatic plant sprinklers for watering the local chrysanthemum horticulture, this PKM activity serves to support farmer organizations in the community. Chrysanthemum and rose picking excursions are one of the tourist attractions in Klino Village, one of the tourist destinations in Bojonegoro. The female farmer organization Blooming Sari is in charge of managing the chrysanthemum cultivation (KTW). Using hoses and padlocks, traditional watering procedures are still used, and they are done in the morning and evening. The approach used in this program is to have casual, one-on-one conversations with farmer groups, followed by observations of field requirements and the creation of tools. The stages of activities completed include site surveys, tool and material analysis, tool creation, tool testing, socialization, monitoring, and PKM program evaluation. This PKM activity resulted to the creation of an IOT-based, smartphone-controllable automatic plant watering solution. There are a number of challenges, including those in tool manufacturing that necessitate numerous trials, pipe installation that requires pipes to match the position point, network limitations, and others. This leads to the conclusion that this PKM activity is effective, capable of resolving issues, and perhaps a solution to the issues facing farmer groups in Klino Bojonegoro village.